Modified multistep model predictive control for three-phase induction motor drive system considering the common-mode voltage minimization - Bao Binh Pho; Nguyen Van Cao; Tran Minh Hoan; Phuong Vu (Institute of Advanced Engineering and Science, 2021)
It is acknowledged that the common-mode voltage may have detrimental effects on an induction motor (IM) drive system if not properly addressed. Therefore, in this paper, a modified multistep model predictive control method for IM drive system considering the common-mode voltage minimization is proposed. This research uses a multi-objective cost function, before applying the Sphere Decoding Algorithm to find the optimal control input. The results show that the proposed control method not only reduces the common-mode voltage significantly but also mitigates the computational burden of the microprocessor without affecting the system performance. The proposed control method is simulated by MATLAB-Simulink for an IM drive system with an 11-level cascaded H-bridge inverter.